High-mixed-voltage analog and RF circuit techniques for nanoscale CMOS - Mak, Pui-In (Analog circuits and signal processing, 2012)
This book presents high-/mixed-voltage analog and radio frequency (RF) circuit techniques for developing low-cost multistandard wireless receivers in nm-length CMOS processes.  Key benefits of high-/mixed-voltage RF and analog CMOS circuits are explained, state-of-the-art examples are studied, and circuit solutions before and after voltage-conscious design are compared. Three real design examples are included, which demonstrate the feasibility of high-/mixed-voltage circuit techniques.    Provides a valuable summary and real case studies of the state-of-the-art in high-/mixed-voltage circuits and systems; Includes novel high-/mixed-voltage analog and RF circuit techniques - from concept to practice; Describes the first high-voltage-enabled mobile-TVRF front-end in 90nm CMOS and the first mixed-voltage full-band mobile-TV Receiver in 65nm CMOS; Demonstrates the feasibility of high-/mixed-voltage circuit techniques with real design examples.